IMPLEMENTASI KONSEP PEMAKNAAN SHALAT IMAM AL-GHAZALI DALAM MEMBENTUK ETIKA AUDITOR UNTUK MEWUJUDKAN KUALITAS AUDIT DI KANTOR AKUNTAN PUBLIK SEMARANG - Husnurrosyidah, Husnurrosyidah; Nadhirin, Nadhirin (EQUILIBRIUM, 2017)
This study aims to implement the concept of meaning of al-Ghazali imam prayer on audit quality through auditor ethics at KAP in Semarang. this research uses qualitative research approach with case study design. Technique of taking data through interview, documentation and observation. Data analysis used is interactive mile mileage technique hubbermens. The result of this research can be seen that the implementation of the meaning concept of al-Ghazali imam prayer can form the quality of auditor through appreciation of Hudhur al-Qalbi concept (concentration) is very needed in a job to avoid error. At-Tafahhum (understanding) is always the first key before we do the work so there is no shift with the other team, it also did not escape the role of concentration. At-Ta'dziem, (feeling the greatness of God), feeling the greatness of God gives motivation to every auditor in his actions so he feels watched in every step. Al-Haibah (amazed by God's majesty and fear of His torment) is the projection of fear. Fear must be owned by all auditors as a follow-up to be careful in the workplace. Ar-Raja ', (hoping the prayers are accepted and rewarded by Allah). This is in line with the fear, the sense of hope is always true in conducting the audit so that responsibility to the service user is fulfilled, especially spirutal responsibility to Allah SWT. Al-Haya '(shame) shame is as a whip of self in order to have good audit quality. Shame if punished, embarrassed if you have low audit work, and embarrassment to have an assessment of a low boss. So it can be concluded that the concept of meaning of al-Ghazali imam prayer can form one's inner behavior. So the quality of audit becomes an integral part with the personal quality of auditors in internalisai meaning of prayer in carrying out the duties as auditors yaang integrity in KAP Semarang